Development of India by Pitambar Pant - Planning Commission (Planning Commission, 1963)
A remarkable feature of the world since the end of the Second World War is the awakening of the people of Asia, Africa and Latin America from the days of political subjugation and economic and social backwardness. There are of course wide differences in their situation, and conditions vary from country to country. In the words of President Kennedy, "many of these live on the frontlines of the long twilight struggle for freedom; others are new nations poised between order and chaos; and the rest are older nations now undergoing a turbulent transition of new expectations".
Planning Commission
Planning Commission